Plasmid curing and the loss of grip – The 65-kb replicon of Phaeobacter inhibens DSM 17395 is required for biofilm formation, motility and the colonization of marine algae - Frank, Oliver; Michael, Victoria; Päuker, Orsola; Boedeker, Christian; Jogler, Christian; Rohde, Manfred; Petersen, Jörn (Systematic and applied microbiology, 2015)
Surface colonization is characteristic for a broad range of marine roseobacters and many strains have been isolated from biofilms, microbial mats and dinoflagellates. Phaeobacter inhibens DSM 17395, one of the best-studied representatives of the Roseobacter group, is an effective colonizer of marine surfaces, but the genetic basis of this trait is unknown. Based on the composition of its 65-kb RepA-I type plasmid that contains more than 20 genes for polysaccharide metabolism, including a rhamnose operon, which is required for O-antigen formation in Escherichia coli, it was hypothesized that this replicon was essential for surface attachment. Accordingly, a holistic approach was taken and the functional role of this extrachromosomal element in P. inhibens was investigated. Plasmid curing was performed with the homologous RepA-I replication system of Dinoroseobacter shibae DSM 16493T. The Δ65-kb mutant completely lost its stickiness and could neither attach to artificial (glass, polystyrene) nor to natural surfaces (algae) and, consequently, its ability to form biofilms was impaired. Surprisingly, the mutant also lost the capacity for flagellar swimming motility required for surface colonization and the dispersal of biofilms. The data clearly showed that the 65-kb replicon of P. inhibens DSM 17395 was a genuine biofilm plasmid-mediating surface attachment. Homologous replicons are widely distributed among Rhodobacterales thus indicating the general importance of extrachromosomal elements for biofilm formation.